Reports on surveillance of antimicrobial resistance in individual countries - Rahal, K; Wang, F; Schindler, J; Rowe, B; Cookson, B; Huovinen, P; Marton, A; Lalitha, M K; Semina, N; Kronvall, G; Guzman, M (Clinical infectious diseases, 1997)
In preparation for the meeting of the World Health Organization Working Group on Monitoring and Management of Bacterial Resistance to Antimicrobial Agents, representatives of 10 countries were asked to provide brief reports on the status of surveillance in their countries. Some gave extensive information on the methods used to test susceptibility of nosocomial pathogens to a variety of antibiotics; some described in detail the network of reference laboratories available to hospitals and individual clinicians for monitoring, identifying, and testing infectious agents; others chose to describe how their countries deal with the resistance of the most frequently isolated pathogen to a commonly used drug. The following summary of these reports shows the broad range of problems encountered and solutions undertaken by these 10 countries in dealing with the increasingly alarming problem of bacterial resistance to antimicrobial agents.
Keywords: Švédsko; Gram-Negative Bacterial Infections; United Kingdom; China; Venezuela; India; Finland; Global Health; celosvětové zdraví; lidé; gramnegativní bakteriální infekce; Alžírsko; Anti-Bacterial Agents; Drug Resistance, Microbial; Spojené království; Algeria; grampozitivní bakteriální infekce; Humans; Gram-Positive Bacterial Infections; Sweden; Bacteria; Czech Republic; Russia; Čína; Hungary; Česká republika; Maďarsko; antibakteriální látky; Indie; antibiotická rezistence; Rusko; Finsko